2018
DOI: 10.1037/amp0000167
|View full text |Cite
|
Sign up to set email alerts
|

Community-based participatory research (CBPR): Towards equitable involvement of community in psychology research.

Abstract: Community-based participatory research (CBPR) answers the call for more patient-centered, community-driven research approaches to address growing health disparities. CBPR is a collaborative research approach that equitably involves community members, researchers, and other stakeholders in the research process and recognizes the unique strengths that each bring. The aim of CBPR is to combine knowledge and action to create positive and lasting social change. With its origins in psychology, sociology, and critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
276
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 346 publications
(279 citation statements)
references
References 58 publications
1
276
0
2
Order By: Relevance
“…Both cases utilized participatory action research and design process. Collins et al (2018) suggested several advantages to utilizing communitybased participatory action research (CBPR). First, CBPR is responsive and respectful of individual needs, preferences, and values and can strengthen accountability to clients.…”
Section: Designing and Implementing Community-based Mental Health Intmentioning
confidence: 99%
“…Both cases utilized participatory action research and design process. Collins et al (2018) suggested several advantages to utilizing communitybased participatory action research (CBPR). First, CBPR is responsive and respectful of individual needs, preferences, and values and can strengthen accountability to clients.…”
Section: Designing and Implementing Community-based Mental Health Intmentioning
confidence: 99%
“…Recent trends in interdisciplinary research have emphasized the benefit of participatory research approaches for knowledge enhancement (Collins et al. ; Tebes and Thai ). Incorporating the Muslim community—extra‐academic participants—into the research process can harness a clearer vision for the contribution of ICTs to practical psychology and Islamic religious practice by sketching out the practical needs of the Muslim community.…”
Section: Discussionmentioning
confidence: 99%
“…Principles of community-based participatory action research (CBPR) played a large role in determining how the model would be used (Cacari-Stone, Wallerstein, Garcia, & Minkler, 2014;Collins et al, 2018;Israel et al, 2010;Israel, Eng, Schulz, & Parker, 2012;Israel, Schulz, Parker, & Becker, 1998;Jagosh et al, 2012;Wallerstein & Duran, 2010). CBPR is a partnership approach to research involving the participation of those affected by an issue (Israel et al, 2012).…”
Section: An Iterative Process Of Reflection and Analysismentioning
confidence: 99%
“…The aim is that all partners will contribute their expertise and have a voice in decision-making (Israel et al, 1998). There is growing evidence that CBPR is a viable approach to eliminating disparities in such fields as health, social services, and public policy (Amendola, Nazario, & Sanchez, 2016;Collins et al, 2018;Israel et al, 2010). A key aspect of CBPR is recognizing power dynamics involved within research relationships involving communities that face marginalization and inequities (Muhammad et al, 2015).…”
Section: An Iterative Process Of Reflection and Analysismentioning
confidence: 99%